E-Procurement implementation from quantity surveyors' perspective / Nur Syazrin Mohamad Radzi and Kharizam Ismail - Mohamad Radzi, Nur Syazrin; Ismail, Kharizam (2020)
In 2002, E-procurement was introduced by the government aiming to improve the quality, cost and time of construction projects. However, many problems had arisen such as lack of knowledge, skilled and management which has become an obstacle in the effectiveness of implementation of this system. Therefore, the aim of this study is to recommend solutions of the challenges in adopting e-procurement in order to added knowledge to the QS consultants. In relation to the aim of the research, some objectives have been identified, which are to determine the type of e-procurement currently practiced by the QS consultants, to identify the challenges in implementing e-procurement within QS consultants and to recommend the solutions to overcome the challenges in implementing eprocurement. This research was conducted using quantitative method. The questionnaire was distributed through online. 68% of the respondents responded to the questionnaire. The questionnaire was distributed to QS consultants in Petaling Jaya, Selangor. The data was then analysed using the SPSS. The result shows that most of the companies are using this types of e-procurement. Furthermore, most of the challenges chosen are lack of top management support to move towards e-commerce and lack of best practice studies and pilot projects. As a result, from research questionnaire, the most agreed solution is the system and data components of the eprocurement technology should be well protected. In conclusion, the findings of this study will encourage construction industry players in implementing and using e-procurement.